2000
DOI: 10.1074/jbc.275.18.13789
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of C-terminal Src Kinase Blocks 14,15-Epoxyeicosatrienoic Acid-induced Tyrosine Phosphorylation and Mitogenesis

Abstract: We have previously reported that 14,15-epoxyeicosatrienoic acid (14,15-EET) is a potent mitogen for the renal epithelial cell line, LLCPKcl4. This mitogenic effect is dependent upon activation of a protein-tyrosine kinase cascade that results in activation of mitogenactivated protein kinase and phosphatidylinositol 3-kinase. Because of suggestive evidence that 14,15-EET also activated Src in these cells, we stably transfected LLCPKcl4 with an expression construct of the C-terminal Src kinase (CSK), which inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 34 publications
(35 reference statements)
1
57
0
Order By: Relevance
“…A body of data accumulated in the past several years indicates that the COX, LOX, and CYP metabolites of arachidonic acid are involved in the maintenance of survival and proliferative capacities of various types of normal and cancer cells and play (2,4,5,(12)(13)(14)(15)(16)(17)(18)(19)(20). Despite these evidences linking arachidonic acid metabolites to the development of various cancers including colon and prostate cancers and vessel wall diseases, very little is known with regard to the mechanisms by which eicosanoids influence these lesions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A body of data accumulated in the past several years indicates that the COX, LOX, and CYP metabolites of arachidonic acid are involved in the maintenance of survival and proliferative capacities of various types of normal and cancer cells and play (2,4,5,(12)(13)(14)(15)(16)(17)(18)(19)(20). Despite these evidences linking arachidonic acid metabolites to the development of various cancers including colon and prostate cancers and vessel wall diseases, very little is known with regard to the mechanisms by which eicosanoids influence these lesions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these lipid molecules have been reported to mediate various intracellular signaling events in response to different stimulants (7)(8)(9)(10)(11)(12). Studies over the past several years also suggest that the COX, LOX, and CYP metabolites of arachidonic acid stimulate the proliferative capacity of various cell types and play a role in tumor progression (13)(14)(15)(16)(17)(18)(19)(20). In addition, eicosanoids have been shown to be associated with the pathogenesis of vascular diseases such as atherosclerosis and restenosis (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…This cDNA then was cloned into the NotI and HindIII sites of the mammalian expression vector pRc/CMV (Invitrogen, San Diego, CA) (21). A total of 1 g/ml of this AT1R cDNA construct or empty pRc/CMV vector alone was used for transfection into LLCPKcl4 cells using LipofectAMINE (Life Technologies, Inc.), and G418-resistant individual clones were isolated as described (19 …”
Section: Stable Transfection Of Ang II Subtype 1 Receptormentioning
confidence: 99%
“…This subclone retains many characteristics of renal proximal tubule epithelial cells but does not express Ang II receptors, unlike the parental LLC-PK1 cells (16). This well-characterized proximal tubule epithelial cell line was cultured routinely as described previously (17)(18)(19)(20).…”
Section: Cell Culturementioning
confidence: 99%
“…This effect was blocked by inhibitors of P450 activity, indicating that the effects of econazole we see in HSWP cells may be at the level of production of EET isoforms rather than as a direct block of the tyrosine kinase. Studies in renal epithelial cells have suggested that the tyrosine phosphorylation induced by 14,15 EET is mediated by src kinase, since EET stimulated src kinase activity (Chen et al, 1998), and that overexpression of C-terminal src kinase blocks 14,15 EET-induced tyrosine phosphorylation (Chen et al, 2000). Therefore, it is tempting to speculate that the cytochrome P450 enzyme activated by Ca 2+ store depletion generates EET isoforms, which then activate srcfamily tyrosine kinases and subsequently open store-operated calcium channels.…”
Section: Discussionmentioning
confidence: 99%